Ibn Rusyd al-Qurtubi wa Manhajuhu al-Fiqhi fi Kitabihi "Bidayah al-Mujtahid" - Sujiat Zubaidi (TSAQAFAH, 2012)
So far, studies focusing on the pattern of Ibn Rusyd’s thought are less performed. Whereas, according to Muhammad Abduh, it is important  to intensively study it, so that there is a balance with his brilliant thought  of philosophy. In this research, the author tries to analyze the patterns of philosophical thought of Islamic jurisprudence of Ibn Rusyd in his book “Bidayah al-Mujtahid”. This short study records many characteristics of his genuineIslamic jurisprudence thoughts namely the presence of strong interrelation and intermediation among jurists, by comparing various opinions of the scholars, followed with istidlal, to the al-khuruj min al-khilaf and tarjih concept. Although earning many praises from many scholars such as Ibn Taymiyya, Ibn Qayyim and Al-Syatibi as contained in his work al-Muwafaqat, however, he also suffered from number of critics due to his preference to the opinions of Imam Malik. Interestingly, Bidayah al-Mujtahid was written by Ibn Rusyd as a critique against Al-Wajiz of Al-Ghazali which is according to Ibn Rusyd it inclines to only one school of thought of Islamic jurisprudence namely Imam Syaﬁ’i. Furthermore, he did also to the same thing to the philosophy of Al-Ghazali in his famous work, Tahafut al-Tahafut.